Institute of Metals Division - Hardness and Creep under Spherical Indentation (TN) - H. D. Merchant (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1964)
NUMEROUS publications have examined hot hardness of metals and alloys. Some have studied creep in long-time hardness tests, few of which, however, were tested under a spherical indentor. 1-3 The results of Mulhearn and Tabor' indicate a parabolic-type creep for indium and lead, whereas Moore and Tabor2 how a logarithmic-type creep for indium. Similar semilog relationships between hardness and time have been found by Goffard and wheeler3 for magnesium, aluminum, and their alloys. In this note, the elevated-temperature hardness of some complex alloys, shown in Table I, was examined to discover whether any basic information about the deformation behavior of the alloys could be obtained. One of the alloys, H-13 alloy steel, was tested for short-time creep tests to examine the hardness-time relationship at various temperatures. A standard Brinell Hardness Tester, mounted with an appropriate furnace and 99 pct A12O3 poly-crystalline indentor, was employed for the purpose. The alloys were tested at temperatures from room to 1400°F for 30 sec under 1500-kg load. The creep studies were conducted for about 8500 sec at 7l°, 500°, 1000°, and 1200°F. For constants A and B, a relationship of the type H = Aexp(-BT) [ll was obtained for all alloys between hardness, H, and temperature, T. In the semilogarithmic plot, the data points for each alloy were arranged into two groups, each group on a straight line with a specific set of A and B values. These results are in agreement with many such observations on hot hardness, notably those of Westbrook for pure metals,4 The thermal softening coefficient, B, and transition temperature, Tt, for various alloys are shown in Table I. The change in slope around the transition temperature suggests an apparent change in the mechanism of deformation, probably from the shear (below Tt) to the diffusion type of mechanism. At the temperatures above Tt, for constants A' and B, a relationship of the type was obtained between H and T, Fig. 1. The nature of the equation, where R is gas constant, suggests the possibility of a thermally activated mechanism of deformation above Tt. The constant B' may hence be defined as the apparent activation energy of indentation. The B' values of various alloys are shown in Table I. A plot of B vs B' gives a curvilinear relation shown in Fig. 2. The indentation-creep data for H-13 alloy steel is shown in Fig. 3. At 71" and 500°F, the creep initially follows the logarithmic time law. However, the indentation size stabilizes after 7 sec at 71°F, and after 10 sec at 500°F. Further increase in loading time has no effect on indentation size. The creep of 1000° and 1200°F follows the logarithmic time law for the first 1000 sec, after which the